The Influence Socio-Economics Backgrounds To Students’ Academic Performance - Lianah The; Arnold Surya Nugroho; Oey Hannes Widjaya (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Indonesian students studying at Curtin University come from different socio-economic backgrounds. Their present socio-economic status was measured by income which is for the survey purposes identified with their scholarships. The aim of the research was to examine and compare the manner in which income as a socio-economic variable had effects on their academic performance. A questionnaire was used as a method for research and students were treated individually. Findings indicated that although not significantly, performance was influenced by income. Background factors, size of family, parents’ occupation and education, area of origin were found to influence the performance in a positive way, also. Survey have found a problem with language which was opposite to previous research. The future investigation on a larger sample may be useful.